Indonesia Economic Quarterly, December 2017 : Decentralization that Delivers - World Bank (World Bank, Washington, DC, 2018)
The Indonesian economy strengthened modestly in third quarter(Q3). Economic growth was supported by higher commodity prices, stronger global growth, rebounding international trade, and relatively accommodative monetary and financial conditions. At the same time, domestic conditions improved, with tentative green shoots in private consumption and stronger domestic demand overall. This article addresses three main questions: (i) what happened to local service delivery during decentralization? (ii) how do we move the needle on local government performance in terms of provision of local services? and (iii) what design mechanisms can incentivize local leaders and sub-national governments to improve local service delivery? The authors offer three key policy recommendations to help align incentives to promote service delivery performance by local leaders and public officials: i) implementing good practices for evaluating local government performance; ii) embedding results-orientation into intergovernmental fiscal transfers;l and iii) use transparent and comparative local government performance data to stimulate citizen engagement.